Potential organ donors after Out-of-Hospital Cardiac Arrest during a ten-year period in Stockholm, Sweden. (April 2019) - af Geijerstam, P.; Forsberg, S.; Claesson, A.; Djärv, T.; Jonsson, M.; Nordberg, P.; Tibell, A.; Rosell Ortiz, F.; Ringh, M.
Abstract: Background: Donation after brain death (DBD) is current praxis in Sweden. Circulatory death is far more common. Donation from patients suffering Out-of-Hospital Cardiac Arrest (OHCA) may have the potential to increase the organ-donor pool. The aim of this study was to describe the potential donor pool and its characteristics if uncontrolled donation after circulatory death (uDCD) were to be implemented in the metropolitan area of Stockholm, Sweden. Methods: A retrospective analysis was made using data from the Swedish Register for cardiopulmonary resuscitation (SRCR) between 2006 and 2015. Evaluation of potential organ donors was made using selection criteria from five previously published protocols concerning uDCD. Results: When applying different criteria from each of the five studied protocols in a total of 9, 793 cases of OHCA, between 7.5% (n = 732) and 1.5% (n = 150) of the patients were found to be potential candidates for uDCD. The median age of the sampled uDCD candidates in each protocol was between 48 and 57 years. Male donors were found in 67–76% of all cases. Conclusion: Although not taking important real-life limitations into account, our results indicate that implementation of a uDCD programme may substantially increase the number of potential organ donors in Stockholm.